Modification of mandibular plates as an alternative for sternal fixation - Pakubuana, Muhammad Alif; Nugraha, Aswin; Bermansyah; Satria, Gama; Umar, Ahmat; Tobing, Arie Hasiholan Lumban; Nasution, Indra Hakim (Journal of Indonesia Vascular Access, 2024)
Introduction: The use of metallic wires for sternal closure after coronary artery bypass grafting (CABG) is standard practice, but it can lead to rare complications such as subsequent sternal wound dehiscence. These complications necessitate surgical revisions, prolong hospital stays, and increase the risk of morbidity and mortality. The following case report presents a patient who underwent modification of mandibular plates as an alternative for Sternal Fixation. Cases: A 55-year-old female patient with a history of severe coronary artery disease (CAD 3VD) underwent coronary artery bypass grafting (CABG). Postoperatively, she developed a sternal dehiscence, resulting in a sternal fracture. The patient underwent two revisions. The first revision concerns potential damage to the internal mammary artery with the Robicsek technique led to multiple fixations using PDS and large PGA 1 sutures. In the 2nd revision, consequently, the sternum was stabilized with three plates and screws on the ribs in the healthy rib area (sternochondral junction) combined with wire. Additionally, the patient had a history of hypertension, type 2 diabetes mellitus, refractory hypoalbuminemia, postmenopausal osteoporosis, and potential hormonal imbalances. In a recent presentation, a clinical examination revealed a fully conscious patient with stable vital signs and minimal drainage from the sternotomy wound. The treatment plan included close observation of the surgical wound, administration of Amikacin (antibiotic), and supportive therapies such as pain management, glycemic control, and inhalation therapy. She was scheduled for outpatient follow-up with a cardiologist for further cardiac monitoring. Conclusion: The case study highlights the complexities of managing sternal wound complications in cardiac surgery patients with additional health concerns. Innovative solutions like mandibular plates may be particularly beneficial for stabilizing the sternum and promoting recovery in post-CABG patients with crushed sternums and complicating factors such as hypertension, diabetes, and refractory hypoalbuminemia, along with postmenopausal osteoporosis and potential hormonal imbalances.